Traduzione di A presença dos dias / La presenza dei giorni - Alves, Adalberto (Studi di Traduzione Letteraria Lusofona, 2020)
Adalberto Alves is an internationally renowned Portuguese poet, translator and arabist essayist and he is the author of a wide literary activity. The collection of aphorisms A presença dos dias / La presenza dei giorni is presented here for the first time in Italian translation. It is one of his most fascinating literary works aimed at those who want to know the western and eastern philosophical world of Adalberto Alves.